Consumer Behavior of Halal Skincare Products Reviewed from the Theory of Planned Behavior Approach - Stefani Maria Wibisono; Evi Rinawati Simanjuntak (Journal of Accounting and Finance Management, 2025)
This study aims to analyze consumer behavior in purchasing halal skincare products in Indonesia using the Theory of Planned Behavior (TPB) approach. The research is motivated by the growing awareness of halal-certified cosmetic products, while a gap remains between consumers' intentions and actual purchasing behavior. This study examines the effects of attitude toward behavior, subjective norms, and perceived behavioral control on purchase intention, as well as the influence of purchase intention on buying behavior. Furthermore, it explores the moderating role of religiosity in the relationship between the three TPB constructs and purchase intention. A quantitative research method was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Data were collected through an online questionnaire from 220 Muslim consumers in West Java who had purchased halal skincare products. The results of the study indicate that attitude toward behavior, subjective norms, and perceived behavioral control have a positive and significant effect on purchase intention. Religiosity is proven to moderate the influence of attitude toward behavior and subjective norms on purchase intention, but does not moderate the relationship between perceived behavioral control and purchase intention. Furthermore, purchase intention has a positive and significant effect on buying behavior, confirming that intention is the main predictor of actual purchasing behavior.